2006
DOI: 10.1089/aid.2006.22.401
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of HIV-1 Subtype C Primary Isolates by Expressed Small Hairpin RNAs Targeted togag

Abstract: Discovery of sequence-specific silencing by activating the RNA interference (RNAi) pathway has led to exciting new strategies for treating infection with human immunodeficiency virus type 1 (HIV-1). Of the HIV-1 subtypes, C is especially common in areas of the world that are worst affected. Although prone to mutation, genome plasticity of this subtype is limited in functionally important regions. We identified conserved sequences within the HIV-1 subtype C gag open reading frame and assessed whether they are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…2 d). Also, previous studies by others [ 33 , 34 ] and our group [ 13 ] showed no in vitro evidence of endogenous type I interferon responses after transduction with lentiviral vectors. The fact that exogenous IFN-α does not have an apparent impact on LV transductions makes a combined approach feasible.…”
Section: Discussionmentioning
confidence: 64%
“…2 d). Also, previous studies by others [ 33 , 34 ] and our group [ 13 ] showed no in vitro evidence of endogenous type I interferon responses after transduction with lentiviral vectors. The fact that exogenous IFN-α does not have an apparent impact on LV transductions makes a combined approach feasible.…”
Section: Discussionmentioning
confidence: 64%
“…Alterations in the RNA folding and structure of these regions can, however, lead to RNAi-resistance [ 92 , 93 ]. Alternatively, the targeting of genes that encode the structural and enzymatic proteins required for viral assembly and infection (including gag , pol , vif , and env ) is effective, despite the fact that these genes are not found in all transcripts [ 94 97 ]. While the integrase and reverse transcriptase proteins are targeted by different classes of antiretroviral drugs, the coding regions of these proteins can also be targeted by RNAi.…”
Section: Rna Interference Approaches For Hiv-1 Treatmentmentioning
confidence: 99%
“…Jacque et al showed siRNA-based inhibition of early and late stages in replication of HIV that made synthesis of DNA from RNA impossible. By now exist several viral sequencestargets that are attacked by specific to them siRNAs: Gag [99] and Env [100], gene of reverse transcriptase Pol [99], genes coding for regulatory proteins-Tat, Rev, Nef and Vif [101].…”
Section: Antiviral Gene Silencing In Invertebrates Insectsmentioning
confidence: 99%